Standards rule? Regulations, literacies and algorithms in times of transition - Ribak, Rivka; Bohbot, Hagar; Davidson, Roei; Marciano, Avi; Ringel, Sharon; Ziskind, Neta; Turow, Joseph (AoIR Selected Papers of Internet Research, 2016)
In this panel we seek to reflect upon the theme "internet rules" by drawing on the notion of standards, developed in Science and Technology Studies. The work of Susan Leigh Star lays a foundation for considering the relationships between rules, standards and algorithms as forms of infrastructure. In the panel, we explore the production of standards as they become transparent infrastructures, heeding Star and Lampland’s call to restore these standards’ "historical development, their political consequences, and the smoke-filled rooms always attached to decisions made about them" (2009:13). Standards – and algorithms – are rarely queried, as they promise and embody efficiency and order. Indeed, modernity may be described as a concentrated, relentless effort to contain the accidental, the arbitrary, the residual; to categorize, order, and routinize the unexpected; and to preclude the exceptional and unpredictable (Bauman, 1991) – in a word: to standardize. As Larkin writes, it is difficult to separate an analysis of infrastructures such as standards from the modernist belief that by promoting order, "infrastructures bring about change, and through change they enact progress, and through progress we gain freedom" (2013:332). It is ironic, then, that standards are distributed unevenly across the sociocultural landscape, that they are increasingly linked and integrated with one another, and that they codify, embody or prescribe social values that often carry great consequences for individuals and groups (Star and Lampland, 2009:5). In this context, the four papers and the moderator of this panel explore the meaning of contemporary standardization practices in such diverse fields as memory applications, crowd funding, biometric identification and national archiving, and internet literacy – viewing them as empirically distinct yet theoretically interrelated attempts to impose order in times of growing uncertainly. Together, they address two tensions that inform contemporary standardization efforts, regarding standards as an encounter between analogue and digital objects and practices; and as dialectic of invisibility and transparency, a pragmatic and symbolic endeavor.